Molecular features of malignant gastric tumors - Yu. A. Gevorkyan; A. V. Dashkov; N. V. Soldatkina; V. E. Kolesnikov; N. N. Timoshkina; D. S. Krutilin; О. К. Bondarenko (Южно-Российский онкологический журнал, 2023)
Gastric cancer is one of the most widespread cancers and makes a significant contribution to the global mortality rate from malignant neoplasms. The late onset of clinical symptoms is the main reason why the disease is often diagnosed at an advanced stage, and this limits the available therapeutic approaches. Despite the fact, that extensive studies have been carried out to identify the mechanisms and markers of the development and progression of the disease, their results are currently not fully included in clinical practice. As a consequence, only marginal improvement in long-term survival has been achieved and patient prognosis remains poor. Understanding the molecular genetic features of gastric malignant tumors can provide insight into their pathogenesis, help identify new biomarkers for prognosis and diagnosis, and identify new therapeutic targets. In recent decades, advances in high throughput sequencing technologies have improved understanding of the molecular genetic aspects of gastric cancer. This review considers molecular level changes, including information on tumor suppressor genes, oncogenes, cell cycle and apoptosis regulators, cell adhesion molecules, loss of heterozygosity, micro-satellite instability and epigenetic aberrations (change in methylation level and modification of histones). The review is also devoted to the molecular aspects of pathogenesis – changes in the signaling pathways involved in the gastric cancer development; the classification of sporadic and hereditary gastric cancer at the molecular genetic level is considered. The characteristics and classification of GC presented in this review at the genetic and epigenetic levels confirms that this disease is heterogeneous. These data can be used both to develop and test potential markers and new targeted therapeutic approaches.